Prototype of autonomous guided vehicle for automatic books storage and retrieval (Revista de Investigaciones Universidad del Quindío, 2014)
The objective of this article is to present the process of designing and implementing a prototype of autonomous guided vehicle (AGV) that must carry out automatic tasks of gathering and location of books in a test environments under controlled conditions. The AGV prototype is a central element of an automatic storage and retrieval system and involves the radiofrequency identification technology with mechatronic elements, of sensors and wireless communication mediated by user interfaces for vehicle monitoring and inventory control. The MiWi P2P communication protocol, which is based on the IEEE 802.15.4 standard, has been chosen to cover wireless communications system in the test environment.
Keywords: Radio Frequency Identification (RFID); and automatic storage system recovery (ASRS); Autonomous Guided Vehicle (AGV); MiWi P2P protocol